2020
DOI: 10.1101/2020.10.26.350116
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of erythroblasts in acute myeloid leukemia causes iron redistribution with clinical implications

Abstract: Acute myeloid leukemia (AML) is a heterogeneous disease with poor prognosis and limited treatment strategies. Determining the role of cell-extrinsic regulators of leukemic cells is vital to gain clinical insights into the biology of AML. Iron is a key extrinsic regulator of cancer but its systemic regulation remains poorly explored in AML. To address this question, we studied iron metabolism in AML patients at diagnosis and mechanisms involved using the syngeneic MLL-AF9-induced AML mouse model. We found that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Thus, the potential of erythroid differentiation of HSCs is commonly suppressed, especially in the bone marrow. EPC precursors, MEPs, are the most suppressed progenitor cells in the bone marrow of mice with hematological malignancies [ 57 , 58 , 136 , 140 , 152 , 153 , 154 ]. In plasma cell myeloma, malignant cell infiltration correlates negatively with hemoglobin concentration, but not with leukocytes or platelet counts, which suggests the selective impairment of erythropoiesis by malignant cells [ 155 ].…”
Section: Cancer-induced Dysregulation Of Erythropoiesismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the potential of erythroid differentiation of HSCs is commonly suppressed, especially in the bone marrow. EPC precursors, MEPs, are the most suppressed progenitor cells in the bone marrow of mice with hematological malignancies [ 57 , 58 , 136 , 140 , 152 , 153 , 154 ]. In plasma cell myeloma, malignant cell infiltration correlates negatively with hemoglobin concentration, but not with leukocytes or platelet counts, which suggests the selective impairment of erythropoiesis by malignant cells [ 155 ].…”
Section: Cancer-induced Dysregulation Of Erythropoiesismentioning
confidence: 99%
“…Suppressed bone marrow steady-state erythropoiesis is a hallmark of inflammation and is caused by the production of pro-inflammatory cytokines and iron sequestration [ 130 , 207 , 228 , 229 ]. Suppression steady-state erythropoiesis is often observed in patients with hematological malignancies [ 136 , 140 , 152 , 153 ] and solid tumors [ 230 ]. As a consequence, stress-erythropoiesis is activated in extramedullary sites to maintain erythroid homeostasis [ 129 ].…”
Section: Cancer-induced Dysregulation Of Erythropoiesismentioning
confidence: 99%
“…found that compared with wild-type littermates, mice lacking hepcidin in colonic tumor epithelium significantly reduced the number, tumor burden and size in the sporadic model of colorectal cancer, whereas lacking of FPN1 led to intracellular iron accumulation and promoted tumor occurrence ( 96 ); Lopes et al. found that acute myeloid leukemia had a unique iron component, mainly manifested as a low expression of transferrin, and high expression of ferritin and hepcidin; notably, these characteristics were not related to inflammation or blood transfusion ( 50 ); Zhao et al. confirmed that hepcidin enhanced the proliferation, migration, and anti-apoptotic capabilities of prostate cancer cells by reducing the expression of FPN1 and increasing intracellular iron level ( 48 ); Additionally, Zhou et al.…”
Section: Iron Metabolism In Cancermentioning
confidence: 99%